Second-line Antiretroviral therapy for HIV-infected children in resource limited settings - Linda Aurpibul (2018)
Pediatric antiretroviral treatment programs have been rolled out in resource limited settings, providing lifesaving treatment to approximately 300,000 HIV-infected children. The standard first-line antiretroviral regimen is a nonnucleoside reverse transcriptase plus 2 nucleoside reverse transcriptase inhibitors (NRTIs). A meta-analysis showed that 70% of children achieved virologic suppression after 12 months of first line therapy. This article presents the challenges in diagnosis of treatment failure in resource limited settings and reviews the current guidelines for management of HIV-infected children with second-line antiretroviral therapy. The details of antiretroviral drugs recommended for second line regimens are summarized. The current standard second-line regimen is a boostedprotease inhibitor-based regimen plus recycling NRTIs. The potential role of new ARV drug classes for second-line regimen is addressed. © 2011 Bentham Science Publishers Ltd.